1997
DOI: 10.2307/3284229
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Species Plasmodium Infections of Humans

Abstract: We analyzed point-prevalence data from 35 recent studies of human populations in which Plasmodium falciparum and one other Plasmodium species were the reported causes of malaria infections. For the P. falciparum-Plasmodium vivax pair, higher overall prevalence in a human population is associated with fewer mixed-species infections than expected on the basis of the product of individual species prevalences. This is not true for P. falciparum-Plasmodium malariae.Our current understanding of parasite communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
2
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 46 publications
5
47
2
1
Order By: Relevance
“…Because circulating RBCs are anucleate and cannot synthesize new surface molecules, receptors that decay cannot be replaced; reticulocyte susceptibility to P. vivax may be related to higher Duffy-antigen density, for instance (20). If RBC susceptibility to P. malariae is related to senescence markers, the accelerated senescence of uninfected RBCs reported with P. falciparum (21) should greatly affect mixed-species infections (22). The common portrayal of P. falciparum as a generalist is complicated by evidence of a seeming preference for young RBCs (23), but more detailed resolution is needed here as well: our model shows that the proportion of RBCs that is in young age classes increases as an infection proceeds.…”
Section: Discussionmentioning
confidence: 99%
“…Because circulating RBCs are anucleate and cannot synthesize new surface molecules, receptors that decay cannot be replaced; reticulocyte susceptibility to P. vivax may be related to higher Duffy-antigen density, for instance (20). If RBC susceptibility to P. malariae is related to senescence markers, the accelerated senescence of uninfected RBCs reported with P. falciparum (21) should greatly affect mixed-species infections (22). The common portrayal of P. falciparum as a generalist is complicated by evidence of a seeming preference for young RBCs (23), but more detailed resolution is needed here as well: our model shows that the proportion of RBCs that is in young age classes increases as an infection proceeds.…”
Section: Discussionmentioning
confidence: 99%
“…vivax/P. malariae species mix, 3,21 suggesting that there is suppression of heterologous parasites. A recent study from a site in PNG neighboring the Wosera with all four human malaria species found no associations.…”
Section: Discussionmentioning
confidence: 99%
“…2 A recent analysis of point-prevalence data from 35 studies of human populations found that for the P. falciparum-P. vivax pair, a higher overall prevalence is associated with fewer mixed-species infections than would be expected on the basis of individual species prevalences. 3 This may in part be due to immunologically cross-reactive epitopes between P. falciparum and P. vivax. 4 However, there was no negative correlation for the P. falciparum-P. malariae, 3 and longitudinal studies indicate that malarial parasites can also favourably affect the host environment for other species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] Various epidemiologic studies involving species co-occurrence recorded fewer mixed infections than expected by chance, suggesting in-host competitive interactions whereby one species has eliminated, or reduced the density of, another species to an undetectable level. [6][7][8][9] These interactions may be mediated by innate host factors that regulate parasite density, 10 parasite metabolism, or factors contributing to the acquisition of heterologous (or cross-species) immunity. 11,12 If heterologous immunity reduces the prevalence of mixed species infections, as has been proposed, [11][12][13] a malaria vaccine may not need to be specific for each species of Plasmodium to be effective.…”
Section: Introductionmentioning
confidence: 99%